Neoliberalization of South Korea Economic Restructuring, Social Precarity, and Post-Developmental Democracy - Chang, Kyung-Sup; Kim, Se-Kyun; Lee, Keun (International Political Economy Series, 2025)
XVIII, 308 p. 3 illus., 2 illus. in color.